1999
DOI: 10.1063/1.370265
|View full text |Cite
|
Sign up to set email alerts
|

A study on the radiation damage and recovery of neutron irradiated vessel steel using magnetic Barkhausen noise

Abstract: In nuclear power plants, neutron embrittlement of pressure vessel steels has been one of the main concerns. The use of micromagnetic Barkhausen emissions is a promising method to monitor the variations in microstructural and subsurface stress states due to their influence on these emissions. Measurements of these emissions can reveal neutron irradiationdegradation in nuclear power plant components. Samples which were irradiated at differentneutron fluences and annealed at different temperatures were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…While it has been frequently shown that mechanical changes in steels, such as those resulting from neutron irradiation, have effects on the major loops of magnetization (e.g., Park et al 2004a;Park et al 1997a)), Barkhausen noise (e.g., (Chang et al 2002;Altpeter et al 2001;Park et al 1999d;Park et al 1999b;Sipahi et al 1994)), impedance spectroscopy (Park et al 2004b;Park et al 2004a), and ferromagnetic resonance (Park et al 2004b;Park et al 2003), only one group has looked at the effects of mechanical changes and precipitation on minor hysteresis loops where the magnetic history is not merely between positive and negative saturations Kobayashi et al 2009Kobayashi et al , 2008Takahashi et al 2005). First order reversal curves (FORCs) are similar to minor loops but consist of only part of the loop.…”
Section: Other Magnetic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While it has been frequently shown that mechanical changes in steels, such as those resulting from neutron irradiation, have effects on the major loops of magnetization (e.g., Park et al 2004a;Park et al 1997a)), Barkhausen noise (e.g., (Chang et al 2002;Altpeter et al 2001;Park et al 1999d;Park et al 1999b;Sipahi et al 1994)), impedance spectroscopy (Park et al 2004b;Park et al 2004a), and ferromagnetic resonance (Park et al 2004b;Park et al 2003), only one group has looked at the effects of mechanical changes and precipitation on minor hysteresis loops where the magnetic history is not merely between positive and negative saturations Kobayashi et al 2009Kobayashi et al , 2008Takahashi et al 2005). First order reversal curves (FORCs) are similar to minor loops but consist of only part of the loop.…”
Section: Other Magnetic Methodsmentioning
confidence: 99%
“…Others realized that micromagnetics could be used for NDE of both nuclear pressure vessel steels (Hsu and Chang 1996;Blaszkiewicz 1996;Ara et al 1996;Dobmann 1994;Kee-Ok et al 1999;Park et al 1999a;Park et al 1999c;Sukegawa et al 2000;Park et al 2000;Kikuchi et al 2006;Park et al 1999d;Park et al 1999b) and power plant steels (Ginsztler et al 1994). Consequently, these steels were soon being routinely investigated using these methods and correlations were developed for hardening and aging.…”
Section: Irradiated Steels -Barkhausen and Other Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection and analysis of the BN have long since been employed for nondestructive sensing of many structural phenomena and physical effects in steels, including austenitic steels, exploiting the dependence of the significant parameters of the noise on specific macroscopic parameters of the material [10][11][12][13][14][15][16][17]. Actually, BN measurements do not provide absolute quantities and one generally looks at the variation of the BN properties with respect to a reference state.…”
Section: Properties and Measurement Of The Barkhausen Noisementioning
confidence: 99%
“…The goal is to use Barkhausen noise emission as the NDE method. It has been shown many times that mechanical changes in steels, such as those resulting from neutron irradiation, have effects on Barkhausen noise (e.g., Sipahi et al 1994;Park et al 1999a;Park et al 1999b;Altpeter et al 2001;Chang et al 2002) and the major loops of magnetization (e.g., Park et al 1997;Park et al 2003;Park et al 2004). Therefore major hysteresis loops, such as those obtained with a vibrating sample magnetometer (VSM) where magnetization is saturated at positive and negative field values, should be obtained on laboratory specimens.…”
Section: Magnetic Measurements For Multi-scale Nde Proof-of-conceptmentioning
confidence: 99%